تفعيل دور وزارة التخطيط في تقييم الجدوى الفنية والاقتصادية للمشاريع المقترحة (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The success of any work requires the development of prior plans for the success of this work as well as providing the necessary sources of funds for the implementation of those plans, where the start of the research problem of delayed sending project proposals to the Ministry of Planning to do its job oversight in checking the technical and economic of those projects feasibility studies, has sought the researcher to the statement of need activating the role of the Ministry of planning in the study of projects before they are implemented and the trade-offs between important projects and projects the most important as they related to the usefulness of the community as well as the economic feasibility evaluation of them in terms of providing material resources required to implement them, as the auditing of projects proposed by the Ministry of planning and contributes significantly to the optimal choice for companies executing and evaluating their implementation capacity. it has reached a researcher to the group's conclusions are: • The failure of the implementation of the companies preparing the technical and economic feasibility studies although she economic units profit.• delay in sending the proposed projects to the Ministry of Planning and lead to the referral of those projects are not able to implement their companies.The most significant recommendations:• The need for the Ministry of Planning and the exercise of legal functions in the approval of the technical and economic feasibility studies prior to referral.• The need to evaluate the bids submitted by the implementation companies more accurately and not to refer the projects to companies offering the lowest bids in case of conflict with the desired specifications.